Global poverty, aid, and middle-income countries: Are the country classifications moribund or is global poverty in the process of 'nationalizing'? - Andy Sumner (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2013)
The majority of the world's poor, by income poverty and multi-dimensional poverty, now live in countries officially classified by the World Bank as middle-income countries. Of course nothing happens when a country crosses a (somewhat) arbitrary threshold in per capita income but it does matter to traditional OECD donors because not only are those thresholds used in numerous and various ways, the crossing of that arbitrary line is viewed as cause enough for some donors to at least consider ending aid. In light of this, this paper considers two competing perspectives on this changing pattern of global poverty: the first is that the thresholds used to classify countries by the World Bank and extensively used by aid agencies, albeit with other indicators and in various ways, are moribund - meaning they do not represent 'poor' or 'non-poor' countries in any meaningful sense any longer (if they ever did) from the point of view of aid donors. The second, and by no means necessarily mutually exclusive, is that global poverty is gradually in the process of 'nationalizing', at least in terms of resources, meaning the bulk of extreme poverty is in developing countries with rapidly rising average incomes and where resource constraints are less pressing. This is not only because of additional resources produced by economic growth, but also because private capital markets can be accessed and thus official development assistance is becoming of lesser importance over time as domestic resources allocation becomes an ever more significant variable. This paper discusses both of these perspectives in turn and considers the implications for OECD donors, offering options for new/alternative country groupings and three avenues for continued OECD donor engagement with countries that have substantial domestic resources (however that is defined).
Keywords: D63; I32; 330; poverty; inequality; economic development